Someone to watch over me [videorecording (DVD)] - Scott, Ridley; Berenger, Tom, 1949-; Rogers, Mimi; Bracco, Lorraine, 1955- (RCA/Columbia Pictures Home Video, 1999)
A stunning New York socialite and a down-to-earth city cop are caught in a deadly web of illicit passion and heart-stopping suspense in this taut, stylilsh thriller. A detective finds his life turned upside down when he is assigned to protect a beautiful eyewitness to a brutal murder.